AKURANSI ARIMA DALAM PERAMALAN INFLASI KOTA BANDUNG - Muhamad Nawawi (Jurnal Manajemen Informatika (JAMIKA), 2017)
Inflation is as one of economic development indicator has an important role to public’s economic prosperity in each country. Inflation rate controlling should be running in order to economic stability .This research aims to forecast inflation of Bandung City using ARIMA Method is suitable for time series data such as inflation rate. Researcher taken data as much as 10 years of inflation rate of Bandung City from January 2006 to December 2015 to forecast inflation rate on next 12 months. The tool using Minitab version 15.0.Result of research shows that sum of data did not influence on accuracy of forecast. It seen on Mean Absolut Percentage Error (MAPE) number tend to not patterned. It is showed on the smallest MAPE value (0,0082) in Forecasting number IV (using 84 data). Moreover, ARIMA shows that longer forecast period is linear to more deviated forecast.